2017
DOI: 10.1016/j.jegh.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance detection and mutation patterns of multidrug resistant tuberculosis strains from children in Delhi

Abstract: A total of 312 sputum samples from pediatric patients presumptive of multidrug resistant tuberculosis were tested for the detection of drug resistance using the GenoTypeMTBDRplus assay. A total of 193 (61.8%) patients were smear positive and 119 (38.1%) were smear negative by Ziehl-Neelsen staining. Line probe assay (LPA) was performed for 208 samples/cultures (193 smear positive samples and 15 cultures from smear negative samples). Valid results were obtained from 198 tests. Of these, 125/198 (63.1%) were sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…The prevalence of childhood TB with resistant strains is indicative of household contact [ 11 ], thus making screening of children essential in limiting the pediatric spread of TB. Moreover, for children, other sampling techniques need to be standardized as young children may not be able to expectorate [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of childhood TB with resistant strains is indicative of household contact [ 11 ], thus making screening of children essential in limiting the pediatric spread of TB. Moreover, for children, other sampling techniques need to be standardized as young children may not be able to expectorate [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 A study from Delhi among children with a presumptive diagnosis of multidrug-resistant (MDR) TB, 61.8% of the sputum samples were smear-positive by ZN staining and 92.8% were positive by LPA. 20 The higher sputum smear and LPA positive results of this study, when compared to ours, was not surprising because their study population was already those with a presumptive MDR-TB. All the above three studies [18][19][20] used LPA to identify MTB drug resistance, whereas, in the present study, we used LPA as a tool for detecting MTB to improve the diagnosis of PTB in children.…”
Section: Discussionmentioning
confidence: 39%
“…“Our studies have found that its incidence among children in Mumbai has increased from 5% in 2007-2010 to 10% in 2013-2016, and continues to grow.”2…”
Section: Nine Countriesmentioning
confidence: 99%